Pengaruh Metode Bermain Peran terhadap Peningkatan Percaya Diri pada Anak Usia Pra Sekolah (4-5 Tahun) di Pendidikan Anak Usia Dini Insan Harapan Klaten - Utami, Rafida Wahyu Tri; Hanafi, Mohammad; Kriswoyo, Pramono Giri (Jurnal Keperawatan Soedirman, 2017)
Roleplay metode is one of ways to increase self esteem in in preschool children. The lesson of pre school children (4-5 years old) is the most basic lesson, it means it’s a critical range to the next step. Roleplay has an education character. The aims of this study were to find any influence of roleplay to increase self esteem in pre school children. This method was pre experimental with one group pre test post test design. The analysis in this study used Wilcoxon test. The sample were 20 person who has age between 4-5 years old. The result shows that after finished the roleplay, children who has high self esteem 12 person (60 %) is more than children who has moderate self esteem 8 person (40 %). The result shows p value 0.000 before and after role play. It means there is a difference betwen self esteem before and after do a roleplay.It concluded there’s a significant influence between rol play method to increase self esteem among pre school children (4-5 years old) Insan harapan at klaten.